LEOPARD Syndrome with APS-2 - Rahman, SI; Pathan, MF; Huq, NA; Agarwala, BK (Journal of Dhaka National Medical College & Hospital, 2019)
LEOPARD syndrome is a phenotypic expression of mutations in several genes: PTPN11, RAF1 and BRAF. This rare autosomal dominant disorder is characterized by high variability of clinical manifestations. Here we report a case of LEOPARD syndrome with APS type -2. A 28 years old lady known diabetic and hypothyroidism presented with us recurrent abdominal pain and vomiting along with uncontrolled blood sugar. She is a third issue of consanguineous marriage. On query her mother gave H/O primary amenorrhea and hearing loss. On examination there is ocular hypertelorism, widely spaced nipple, loss of scalp hair, eye brow and tooth. There are multiple skin lentigines( dark skin spot), lack of secondary sexual characteristics with tanner stage-1. After evaluation she was found hypergonadotrophic hypogonadism, acute on chronic pancreatitis and dyslipidemia. Her conservative management was given for pancreatitis. Hormone replacement therapy was started and advised to continue levothyroxine and insulin. Also advised for regular follow-up on endocrine OPD of BIRDEM general hospital. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 36-37